2019
DOI: 10.2134/agronj2019.02.0095
|View full text |Cite
|
Sign up to set email alerts
|

World Sulfur Use Efficiency for Cereal Crops

Abstract: Sulfur (S) is an essential plant nutrient needed for higher crop yields and improved nutritional value. In recent decades, the occurrence of S deficiency has increased and fertilizer S use may steadily increase. This may lead to inefficient crop utilization of S and result into negative footprints on the environment. The objective of this work was to estimate world fertilizer sulfur use efficiency (SUE) for major cereal crops grown around the world. A 10‐yr data set (2005–2014) was obtained from the Food and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 57 publications
3
32
0
1
Order By: Relevance
“…Global estimates of phosphorus (P) (Dhillon et al, 2017), potassium (K) (Dhillon et al, 2019), and sulfur (S) (Aula et al, 2019) use efficiencies in cereal crops have been found to be highly variable from one year to the next. Phosphorus use efficiency in cereal crops was found to be 16% on average over a 53‐yr period (range, 12–21%) (Dhillon et al, 2017).…”
Section: Entropy and Randomnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Global estimates of phosphorus (P) (Dhillon et al, 2017), potassium (K) (Dhillon et al, 2019), and sulfur (S) (Aula et al, 2019) use efficiencies in cereal crops have been found to be highly variable from one year to the next. Phosphorus use efficiency in cereal crops was found to be 16% on average over a 53‐yr period (range, 12–21%) (Dhillon et al, 2017).…”
Section: Entropy and Randomnessmentioning
confidence: 99%
“…Similarly, over a 55‐yr period, potassium use efficiency averaged 19% (range, 15–26%) (Dhillon et al, 2019). Likewise, sulfur use efficiency averaged 18% (range, 14–22%) (Aula et al, 2019). In summary, these citations reflect the randomness and unpredictable nature of yields across the globe and associated use efficiencies.…”
Section: Entropy and Randomnessmentioning
confidence: 99%
“…Moreover, several studies have shown that sulfur increased wheat grain yield, gluten, cysteine, and methionine [16]. Nonetheless, sulfur levels in the soil were found to be declining during the last decade [17]. The reasons for sulfur declining are; using new, highly purified fertilizers with less sulfur [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As a macronutrient, the average concentration of S in plant tissues for adequate growth is relatively high (around 0.1 to 0.5% of plant dry weight) [4]. However, S de ciency has become a rising problem in crops primarily due to decreases in atmospheric S inputs caused by strict industrial emission regulations and changes in agronomic practices, including the use of fertilizers with reduced S compositions, reduction in the use of S-containing fungicides and intensive cropping systems that remove S from the soils [5]. Prolonged S de ciency causes a reduction in photosynthetic rate, chlorophyll levels and amino acid contents, leading to growth retardation and diminished yield, nutritional quality and taste of crops [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, S de ciency has become a rising problem in crops primarily due to decreases in atmospheric S inputs caused by strict industrial emission regulations and changes in agronomic practices, including the use of fertilizers with reduced S compositions, reduction in the use of S-containing fungicides and intensive cropping systems that remove S from the soils [5]. Prolonged S de ciency causes a reduction in photosynthetic rate, chlorophyll levels and amino acid contents, leading to growth retardation and diminished yield, nutritional quality and taste of crops [5][6][7]. Moreover, S-starvation alters the acquisition of other nutrients such as nitrate, phosphate, molybdenum, selenium, and iron [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%